Railway Spare Parts Supplier Selection Using Analytic Hierarchy Process: A Case Study of Rollingstock Spare Parts - Zulkarnain, Nurhannani Fasihah; Abdul Hamid, Nor Aziati; Selimim, Mohamad Ali (Research in Management of Technology and Business, 2025)
The selection of spare parts from railway suppliers is a multifaceted process influenced by various factors, including cost, quality, delivery speed, and supplier reliability. Despite significant advancements in supply chain management and inventory control, notable research gaps persist in this domain. A particular deficiency exists in Malaysia, where there is a lack of focused research on the selection of suitable and dependable suppliers, a challenge frequently encountered by rail operators in the country. This study aims to address this gap by examining the current issues related to the performance of suppliers of rolling stock spare parts for a major railway operator in Malaysia. The research employs the Analytic Hierarchy Process (AHP) to analyze the critical criteria for selecting suppliers of rolling stock spare parts and to propose enhancements to the existing supplier selection process at the operator's maintenance depot. The study specifically targets the electrified multiple unit type 93 version 2 and utilizes a quantitative approach through an online survey questionnaire. The survey was completed by procurement staff, maintenance personnel, warehouse staff, and senior engineers, with a total sample size of 17 respondents, all of whom possess a minimum of three years of experience in asset maintenance and procurement. AHP and pairwise comparison methods were utilized for data analysis and collection. The findings revealed a consistent comparison matrix between the two primary criteria: Inventory Aspect and Maintenance Aspect, with Alternative 1 identified as the optimal choice, thereby suggesting effective strategies for rail supplier selection. In conclusion, rail operators can utilize the ranking criteria established in this study to select the most suitable spare parts suppliers, thereby mitigating risks and enhancing spare parts inventory.